Maternal Schizophrenia and the Risk of a Childhood Chronic Condition. (28th July 2022) - Vigod, Simone N; Ray, Joel G; Cohen, Eyal; Wilton, Andrew S; Saunders, Natasha R; Barker, Lucy C; Berard, Anick; Dennis, Cindy-Lee; Holloway, Alison C; Morrison, Katherine; Oberlander, Tim F; Hanley, Gillian; et al.
Abstract: Background and Hypothesis: Maternal schizophrenia heightens the risk for certain perinatal complications, yet it is not known to what degree future childhood chronic health conditions (Childhood-CC) might arise. Study Design: This population-based cohort study using health administrative data from Ontario, Canada (1995–2018) compared 5066 children of mothers with schizophrenia to 25 324 children of mothers without schizophrenia, propensity-matched on birth-year, maternal age, parity, immigrant status, income, region of residence, and maternal medical and psychiatric conditions other than schizophrenia. Cox proportional hazard models generated hazard ratios (HR) and 95% confidence intervals (CI) for incident Childhood-CCs, and all-cause mortality, up to age 19 years. Study Results: Six hundred and fifty-six children exposed to maternal schizophrenia developed a Childhood-CC (20.5/1000 person-years) vs. 2872 unexposed children (17.1/1000 person-years)—an HR of 1.18, 95% CI 1.08–1.28. Corresponding rates were 3.3 vs. 1.9/1000 person-years (1.77, 1.44–2.18) for mental health Childhood-CC, and 18.0 vs. 15.7/1000 person-years (1.13, 1.04–1.24) for non-mental health Childhood-CC. All-cause mortality rates were 1.2 vs. 0.8/1000 person-years (1.34, 0.96–1.89). Risk for children exposed to maternal schizophrenia was similar whether or not children were discharged to social service care. From age 1 year, risk was greater for children whose mothers were diagnosed with schizophrenia prior to pregnancy than for children whose mothers were diagnosed with schizophrenia postnatally. Conclusions: A child exposed to maternal schizophrenia is at elevated risk of chronic health conditions including mental and physical subtypes. Future research should examine what explains the increased risk particularly for physical health conditions, and what preventive and treatment efforts are needed for these children.